Tunable Q-switched laser using rose gold-based saturable absorber / Adzlan Muhaymin Idris - Adzlan Muhaymin, Idris (2018)
In this dissertation, a tunable laser using rose-gold based saturable absorber (SA) was researched. The SA was prepared using sodium borohydrate (NaBH4) reduction method by mixing Gold (III) chloride trihydrate (HAuCl4) (~50% Au-based), Polysodium-4- styrenesulfonate (PSSS), tri–sodium citrate (TSC) (Na3C6H5O7), and NaBH4. Ring cavity laser setup was deployed to generate train of pulses for optical parameters measurement. Three experiments were conducted where the output lasers were tuned to 1539.88 nm, 1550.17 nm, and 1560.21 nm wavelength. For each experiment, input pump power was increased in step of 10 mW starting from the lowest threshold power where the SA would start to act as a Q-switch. The lowest and highest thresholds were different for each output wavelength, producing different power pumping range. The recorded ranges for input pump power were 35 mW to 115 mW (1539.88 nm), 45 mW to 165 mW (1550.17 nm), and 40 mW to 170 mW (1560.21 nm). Peak output powers monitored for each laser were 1.17 mW (1539.88 nm), 2.64 mW (1550.17 nm), and 2.36 mW (1560.21 nm). Laser efficiencies were obtained by measuring the slope when plotting output power to input pump power. Obtained laser efficiency values were 1.296 % (1539.88 nm), 1.900 % (1550.17 nm), and 1.612% (1560.21 nm). It was concluded that the SA was best-suited to be paired with Erbium-doped fiber laser (EDFL) for laser generation at 1550 nm. Keywords: tunable laser, rose gold, saturable absorber, Q-switched, laser efficiency.